(untitled) (Delta Medical College Journal, 2024)
Background: Acute confusional state (ACS) or delirium is a clinical condition categorized by troubled consciousness, cognitive function, or perception. The key to the management of cases of ACS lies in recognizing a cause or other contributing illness and alleviating it. Objective: To evaluate the patients of ACS intending to identify the clinical presentation of the ACS along with the outcome evaluation of its prognostic importance. Materials and method: A total of 50 patients of ACS fulfilling the DSM-4 criteria were enrolled purposively. It was a hospital-based cross-sectional type of observational study conducted among adult patients of more than 18 years of age for nine months period in the medicine department of Dhaka Medical College Hospital. Results: The mean age of patients was 63.18±9.8 years. Majority of the patients (66%) were male. Hypertension was the most common (46%) associated condition followed by obesity (22%). Fever was common in the majority of cases (78%) followed by disorientation (64%). Among the patients with cerebrovascular accidents, 70.59% had multiple infarcts and 29.42% showed hemorrhage in CT scans of the brain. Most of the patient’s (76%) recovery was without any sequelae. Only 6% of patients died during the hospital stay. Conclusion: Acute confusional state (ACS) is among the most common problems in general medicine. Hence, treatment and further workup should run parallel to avoid the morbidity and mortality related to these circumstances. Delta Med Col J. Jan 2021;9(2): 75-79